3x-5y=6

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 3x from both sides of the equation.

-5y=6-3x

Divide each term by -5 and simplify.

Divide each term in -5y=6-3x by -5.

-5y-5=6-5+-3x-5

Cancel the common factor of -5.

Cancel the common factor.

-5y-5=6-5+-3x-5

Divide y by 1.

y=6-5+-3x-5

y=6-5+-3x-5

Simplify 6-5+-3x-5.

Simplify each term.

Move the negative in front of the fraction.

y=-65+-3x-5

Dividing two negative values results in a positive value.

y=-65+3×5

y=-65+3×5

Reorder -65 and 3×5.

y=3×5-65

y=3×5-65

y=3×5-65

Rewrite in slope-intercept form.

y=35x-65

y=35x-65

Using the slope-intercept form, the y-intercept is -65.

b=-65

Find the Y-Intercept 3x-5y=6